Editorial: Cancer Cell Metabolism and Immunomodulation in the Context of Tumor Metastasis - Dong, Qiongzhu; Nelson, Peter J.; Zhao, Yue (Frontiers in Oncology, 2022)
Primary tumor growth and the tumor metastasis are strongly linked to the adaption of the tumor tissues to environmental issues. These can include growth in low oxygen conditions and the selective use of substances for energy needs as well as means to escape detection by the immune system. Metastasis represents the major cause for poor prognosis for patients with cancers. Cancer patients are diagnosed with metastatic disease either at diagnosis of the disease, or later as they emerge during the course of treatment. Metabolic alterations and immune evasion represent some of the hallmark capabilities of tumor cells that develop during multistep metastatic progression. Cancer cells become adapted to survive with an energy supply and additional growth stimuli imparted through the tissue environment during the metastatic process. At the same time, cancer cells evade destruction by the immune system through various adaptions that enables them to progress. Various immune cells and immune processes have been linked to both the inhibition, and promotion, of metastatic processes. Recent advances in immunotherapy and the development of metabolic oncology inhibitors are providing exciting new approaches for the treatment of cancer. As we are learning more about the molecular basis of cancer metabolism and the general biology of the tumor immune microenvironment, novel strategies are emerging that may help prevent or control cancer metastasis. Tumor immunity and metabolism in cancer metastasis was the goal of this research topic.